Silicon-based negative electrode, preparation method thereof and electrochemical device
The negative electrode active material layer and functional coating are combined through thermal rolling technology, which solves the problem of silicon-based negative electrode falling off in lithium-ion batteries due to excessive stress, improves the capacity and cycling performance of the electrochemical device, and is suitable for high energy density systems.
Patent Information
- Application Number
- CN202311264871.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The silicon-based negative electrode falls off in lithium-ion batteries due to excessive stress, resulting in a decrease in the capacity and circulation performance of the electrochemical device and cannot meet the requirements of the high-energy density system.
The negative electrode active material layer is combined with the current collector provided with a functional coating by hot rolling, thereby improving the adhesion between the negative electrode active material layer and the current collector, and improving the problem of falling off of the silicon-based negative electrode during charging and discharging.
The capacity and circulation performance of the electrochemical device are improved, and the peeling force is increased by more than 30%, which is suitable for high-silicon content negative electrode systems.
Smart Images

Figure CN119725403A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrochemical devices, and in particular to a silicon-based negative electrode and a preparation method thereof, and an electrochemical device. Background Art
[0002] Lithium-ion batteries have the advantages of high voltage, high capacity, long cycle life and good safety performance, which makes them have broad application prospects in portable electronic devices, electric vehicles, energy storage, defense industry and many other aspects. They have become a hot spot for research and development of new energy industries that has attracted widespread attention in recent years.
[0003] At present, the most practically used negative electrode materials for lithium-ion batteries are carbon materials, such as natural graphite. Among non-carbon negative electrode materials, silicon has an extremely high theoretical specific capacity and plays an important role in high energy density batteries. In addition, silicon is widely distributed in nature, and its content in the earth's crust is second only to oxygen. Therefore, silicon-based negative electrode materials are a class of high-energy materials with great development prospects. However, silicon has low electronic conductivity and ionic conductivity, resulting in poor kinetic performance of its electrochemical reaction. In addition, silicon-based negative electrodes undergo lithium removal and lithium insertion during the charging and discharging process, causing the volume to shrink and expand continuously, with a volume change of up to 270%. This generates stress between the negative electrode material and the current collector, resulting in the separation of the two, interface contact failure, deterioration of battery performance, and poor cycle life, which ultimately leads to the failure of lithium-ion batteries. Moreover, with the continuous pursuit of battery cell energy density, the content of silicon materials in negative electrode active materials continues to increase, and the existing negative electrodes can no longer meet the requirements of high energy density systems. CN112599778 discloses a silicon-carbon-based negative electrode material and a preparation method thereof, wherein the silicon-carbon-based negative electrode material comprises a silicon material and a carbonaceous layer coated on the surface of the silicon material. Both the silicon material and the silicon-carbon-based negative electrode material have a porous structure, which can alleviate the volume effect during the charging and discharging process to a certain extent and reduce the problem of powdering and shedding of electroactive substances. However, as time goes by, the performance of the battery cell will inevitably deteriorate due to the volume effect, the cycle life will deteriorate, and the lithium-ion battery will eventually fail.
[0004] Therefore, it is of great significance to provide a silicon-based negative electrode with high energy density, good cycle stability and good adhesion. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a silicon-based negative electrode and a preparation method thereof, and an electrochemical device. The silicon-based negative electrode provided by the present application can improve the adhesion between the negative electrode active material and the current collector, and improve the problem of the silicon-based negative electrode falling off from the current collector surface due to excessive stress during the charging and discharging process, thereby improving the capacity and cycle performance of the electrochemical device, and can be applied to high silicon content negative electrode systems.
[0006] In a first aspect, the present application provides a method for preparing a silicon-based negative electrode, wherein the silicon-based negative electrode comprises a current collector, a functionalized coating and a negative electrode active material layer stacked in sequence;
[0007] The preparation method comprises: compounding a negative electrode active material layer on a current collector provided with a functionalized coating by means of hot rolling.
[0008] The present application uses a hot roller pressing method to composite the negative electrode active material layer on a current collector provided with a functionalized coating to prepare a silicon-based negative electrode, which can effectively improve the adhesion between the negative electrode active material layer and the current collector, and improve the problem of the silicon-based negative electrode falling off from the current collector surface due to excessive stress during the charge and discharge process, thereby improving the capacity and cycle performance of the electrochemical device, and can be applied to a high silicon content negative electrode system, specifically:
[0009] The present application adopts a hot rolling method to composite the negative electrode active material layer on a current collector provided with a functionalized coating, thereby improving the adhesion between the negative electrode active material layer and the current collector, and improving the problem of the silicon-based negative electrode falling off from the current collector surface due to excessive stress during the charge and discharge process, thereby improving the capacity and cycle performance of the electrochemical device, and can be applied to a high silicon content negative electrode system. Compared with the ordinary rolling method, the peeling force of the silicon-based negative electrode sheet obtained by the hot rolling method of the present application can be increased by more than 30%.
[0010] As a preferred technical solution of the present application, the temperature of the hot rolling is 60-120°C, such as 70°C, 80°C, 90°C, 100°C, 110°C, etc., preferably 70-90°C.
[0011] When the temperature of hot rolling is within the preferred range, the negative electrode active material layer can be better integrated with the functional coating and have better adhesion, thereby improving the problem of silicon-based negative electrode falling off from the current collector surface due to excessive stress during charging and discharging, thereby improving the capacity and cycle performance of the electrochemical device.
[0012] As a preferred technical solution of the present application, the hot rolling speed is less than 20 m / min, for example, 18 m / min, 16 m / min, 14 m / min, 12 m / min, 10 m / min, 8 m / min, 6 m / min, 4 m / min, 2 m / min, etc.
[0013] When the rate of hot rolling is within the range of this application, the negative electrode active material layer can be better integrated with the functional coating and have better adhesion, thereby improving the problem of silicon-based negative electrodes falling off the surface of the current collector due to excessive stress during the charge and discharge process, thereby improving the capacity and cycle performance of the electrochemical device.
[0014] As a preferred technical solution of the present application, the pressure of the hot roller pressing is 1-10T, such as 2T, 4T, 6T, 8T, etc.
[0015] As a preferred technical solution of the present application, the compaction density of the hot roller pressing is 1.3-1.65g / cm 3 , for example 1.35 g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 wait.
[0016] As a preferred technical solution of the present application, the components of the negative electrode active material layer include a negative electrode active substance, a first binder, a first conductive agent and a plasticizer.
[0017] As a preferred technical solution of the present application, the components of the functionalized coating include a second conductive agent and a second binder.
[0018] The components of the functionalized coating provided in the present application include a second conductive agent and a second binder. The second conductive agent makes the functionalized coating conductive and connects the negative electrode active material layer and the negative electrode current collector. The second binder can be integrated with the first binder in the negative electrode active material layer to form an interpenetrating network of binders, thereby strengthening the interlocking effect between the first binder and the silicon-based negative electrode, improving the adhesion between the negative electrode active material and the current collector, and improving the problem of the silicon-based negative electrode falling off from the current collector surface due to excessive stress during the charge and discharge process, thereby improving the battery capacity and cycle performance.
[0019] As a preferred technical solution of the present application, the first conductive agent and the second conductive agent are independently selected from any one or a combination of two or more of conductive carbon black, conductive carbon fiber, graphene, carbon nanotubes or Ketjen black.
[0020] As a preferred technical solution of the present application, the first conductive agent and the second conductive agent contain the same component.
[0021] As a preferred technical solution of the present application, the first binder and the second binder are independently selected from any one or a combination of two or more of sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylate, polyacrylonitrile (PAN) or styrene-butadiene rubber (SBR).
[0022] As a preferred technical solution of the present application, the first binder and the second binder contain the same components.
[0023] In the present application, when the first binder and the second binder contain the same components, the adhesion between the negative electrode active material layer and the functionalized coating layer is better, which can more effectively improve the adhesion between the negative electrode active material and the current collector.
[0024] As a preferred technical solution of the present application, the negative electrode active material includes graphite, or a combination of graphite and silicon material.
[0025] As a preferred technical solution of the present application, the plasticizer is selected from any one or a combination of two or more of ethylene carbonate, N-methylpyrrolidone, ethylene glycol or isopropanol.
[0026] As a preferred technical solution of the present application, the preparation method includes: mixing a negative electrode active material, a first binder, a first conductive agent, a plasticizer and water to obtain a negative electrode active slurry, coating the negative electrode active slurry on a current collector provided with a functionalized coating, and then performing hot rolling.
[0027] As a preferred technical solution of the present application, the viscosity of the negative electrode active slurry is 2000-8000 cP, for example, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 7000 cP, etc.
[0028] As a preferred technical solution of the present application, the solid content of the negative electrode active slurry is 25-55wt%, for example, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% and the like.
[0029] As a preferred technical solution of the present application, the coating surface density of the negative electrode active slurry is 50-200g / m 2 , for example 60g / m 2 , 80g / m 2 , 100g / m 2 , 120g / m 2 , 140g / m 2 , 160g / m 2 , 180g / m 2 wait.
[0030] As a preferred technical solution of the present application, the mass ratio of the negative electrode active material, the first binder, the first conductive agent and the plasticizer is (90-99):(1-9):(0.5-5):(0.5-5), and the sum of the mass fractions of the components is 100wt%.
[0031] As a preferred technical solution of the present application, based on the total mass of the negative electrode active material as 100%, the content of the graphite is 50-100wt%, for example, 60wt%, 70wt%, 80wt%, 90wt%, etc., and the content of the silicon material is 0-50wt%, for example, 10wt%, 20wt%, 30wt%, 40wt%, etc.
[0032] As a preferred technical solution of the present application, the thickness of the functionalized coating is 0.5-2 μm, for example, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, etc.
[0033] As a preferred technical solution of the present application, the thickness of the negative electrode active material layer is 50-150 μm, for example, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, etc.
[0034] As a preferred technical solution of the present application, the current collector is selected from copper foil or aluminum foil.
[0035] As a specific implementation of the present application, the method for preparing the silicon-based negative electrode comprises the following steps:
[0036] (1) mixing the negative electrode active material, the first binder, the first conductive agent, the plasticizer and water in proportion to obtain a negative electrode active slurry having a viscosity of 2000-8000 cP and a solid content of 25-55 wt %;
[0037] (2) The negative electrode active slurry is coated on a current collector provided with a functionalized coating, and hot roller pressing is performed at 60-120° C. at a rate of ﹤20 m / min, and the compaction density of the negative electrode sheet is 1.3-1.65 g / cm 3 , and obtain the silicon-based negative electrode.
[0038] The present application adopts a hot rolling method to composite the negative electrode active material layer on a current collector provided with a functionalized coating, so that the binder and plasticizer in the negative electrode active material layer are integrated with the binder in the functionalized coating to form an interpenetrating network of the binder, thereby strengthening the interlocking effect between the binder and the silicon-based negative electrode, thereby improving the adhesion between the negative electrode active material in the negative electrode active material layer and the current collector, and improving the problem of the silicon-based negative electrode falling off the surface of the current collector due to excessive stress during the charge and discharge process, thereby improving the capacity and cycle performance of the electrochemical device, and can be applied to a high silicon content negative electrode system.
[0039] The current collector provided with a functional coating described in the present application is not limited in this application and can be purchased or made in-house. As a preferred technical solution of the present application, the present application provides a method for preparing a current collector provided with a functional coating, comprising the following steps:
[0040] (1) mixing a second binder, a second conductive agent and water in proportion to obtain a functionalized slurry having a viscosity of 2000-5000 cP and a solid content of 40-60 wt %;
[0041] (2) The functionalized slurry is coated on a current collector, and dried at 60-120° C. to obtain the current collector provided with the functionalized coating.
[0042] In the second aspect, the present application provides a silicon-based negative electrode obtained by the preparation method described in the first aspect, and the peel strength of the silicon-based negative electrode is 1-20N / m, for example, 2N / m, 5N / m, 10N / m, 15N / m, 20N / m, etc., preferably 10-20N / m.
[0043] The silicon-based negative electrode prepared in the present application can improve the adhesion between the negative electrode active material layer and the current collector, improve the problem of the silicon-based negative electrode falling off from the current collector surface due to excessive stress during the charge and discharge process, and has excellent cycle stability and adhesion. Its peeling force is increased by more than 30% compared with the silicon-based negative electrode obtained by ordinary rolling, which broadens the application scenarios of high silicon content negative electrode systems.
[0044] In a third aspect, the present application provides an electrochemical device, which includes the silicon-based negative electrode described in the second aspect. The electrochemical device provided by the present application has a higher battery capacity and excellent cycle performance.
[0045] As a specific embodiment of the present application, the present application provides a method for preparing a lithium battery, comprising the following steps:
[0046] (1) coating the positive electrode active slurry on the positive electrode current collector and rolling it to obtain a positive electrode sheet;
[0047] (2) preparing a silicon-based negative electrode according to the preparation method described in the first aspect;
[0048] (3) Assembling the positive electrode plate and the silicon-based negative electrode, and performing infiltration, chemical formation, and capacity separation to obtain the lithium battery.
[0049] As a specific implementation of the present application, the positive electrode active slurry includes a positive electrode active material, a third binder and a third conductive agent.
[0050] As a preferred technical solution of the present application, the mass ratio of the positive electrode active material, the third binder and the third conductive agent is (90-99):(1-9):(0.5-5), and the sum of the mass fractions of each component is 100wt%, for example 92:7:1, 95:3:2, 98:1:1, etc.
[0051] As a preferred technical solution of the present application, the positive electrode active material is selected from any one or a combination of two or more of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese iron phosphate, lithium manganese oxide or lithium-rich manganese base.
[0052] As a preferred technical solution of the present application, the third binder is selected from any one of PVDF (polyvinylidene fluoride), PMMA (polymethyl methacrylate), PTFE (polytetrafluoroethylene) or PI (polyimide) or a combination of two or more thereof.
[0053] As a preferred technical solution of the present application, the third conductive agent is selected from any one or a combination of two or more of conductive carbon black, conductive carbon fiber, graphene, carbon nanotube or Ketjen black.
[0054] As a preferred technical solution of the present application, the viscosity of the positive electrode active slurry is 2000-8000 cP, for example, 3000 cP, 4000 cP, 5000 cP, 6000 cP, 7000 cP, etc.
[0055] As a preferred technical solution of the present application, the solid content of the positive electrode active slurry is 65-75wt%, for example, 66wt%, 68wt%, 70wt%, 72wt%, 74wt% and the like.
[0056] Compared with the prior art, the technical solution provided by the embodiments of the present application has the following advantages:
[0057] 1. The present application adopts a hot rolling method to composite the negative electrode active material layer on a current collector provided with a functionalized coating, thereby improving the adhesion between the negative electrode active material layer and the current collector, and improving the problem of silicon-based negative electrodes falling off from the current collector surface due to excessive stress during charging and discharging, thereby improving the capacity and cycle performance of the electrochemical device, and can be applied to high silicon content negative electrode systems.
[0058] 2. The peeling force of the silicon-based negative electrode sheet obtained by hot rolling in the present application can be increased by more than 30% compared with the ordinary rolling method. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0060] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0061] Figure 1 The peeling force test results of the silicon-based negative electrode obtained in Examples 1-7 and Comparative Examples 1-2 of the present application;
[0062] Figure 2 This is a picture of the disassembled negative electrode of the battery obtained by the silicon-based negative electrode of Example 5 of the present application;
[0063] Figure 3 This is a picture of the disassembled negative electrode of the battery obtained from the silicon-based negative electrode of Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0064] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the scheme of the present application will be further described below. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0065] In the following description, many specific details are set forth to facilitate a full understanding of the present application, but the present application may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only part of the embodiments of the present application, rather than all of the embodiments.
[0066] Example 1
[0067] This embodiment provides a silicon-based negative electrode and a preparation method thereof, wherein the silicon-based negative electrode comprises a current collector layer, a functionalized coating layer and a negative electrode active material layer stacked in sequence, the thickness of the functionalized coating layer is 1 μm, the thickness of the negative electrode active material layer is 120 μm, and the current collector is a copper foil;
[0068] The preparation method comprises:
[0069] (1) mixing the negative electrode active material, the first binder, the first conductive agent, the plasticizer and water to obtain a negative electrode active slurry having a solid content of 45% and a viscosity of 4500 cP;
[0070] (2) The negative electrode active slurry was coated on the current collector provided with the functionalized coating, dried, and hot rolled at 80°C at a rate of 3 m / min. The compacted density of the negative electrode sheet was 1.45 g / cm 3 , die cutting to obtain a silicon-based negative electrode;
[0071] The mass ratio of the negative electrode active material, the first binder, the first conductive agent and the plasticizer is 94:4:1.5:0.5, the negative electrode active material is 10wt% of silicon oxide and 90wt% of graphite, the first binder is 30wt% of sodium carboxymethyl cellulose, 40wt% of polyacrylic acid and 30wt% of styrene-butadiene rubber, the first conductive agent is 50wt% of conductive carbon black and 50wt% of carbon nanotubes, the plasticizer is ethylene carbonate, and the components of the functionalized coating on the current collector provided with the functionalized coating include 90wt% of polyacrylic acid and 10wt% of conductive carbon black.
[0072] Example 2
[0073] This embodiment provides a silicon-based negative electrode and a preparation method thereof, wherein the silicon-based negative electrode comprises a current collector layer, a functionalized coating layer and a negative electrode active material layer stacked in sequence, the thickness of the functionalized coating layer is 2 μm, the thickness of the negative electrode active material layer is 80 μm, and the current collector is a copper foil;
[0074] The preparation method comprises:
[0075] (1) mixing the negative electrode active material, the first binder, the first conductive agent, the plasticizer and water to obtain a negative electrode active slurry having a solid content of 25% and a viscosity of 5000 cP;
[0076] (2) The negative electrode active slurry was coated on the current collector provided with the functionalized coating, dried, and hot rolled at 60°C at a rate of 1 m / min. The compacted density of the negative electrode sheet was 1.3 g / cm 3 , die cutting to obtain a silicon-based negative electrode;
[0077] The mass ratio of the negative electrode active material, the first binder, the first conductive agent and the plasticizer is 92:6:1:1, the negative electrode active material is 50wt% of silicon oxide and 50wt% of graphite, the first binder is 30wt% of sodium carboxymethyl cellulose, 40wt% of polyacrylate and 30wt% of styrene-butadiene rubber, the first conductive agent is 30wt% of conductive carbon fiber, 40wt% of conductive carbon black and 30wt% of carbon nanotubes, the plasticizer is 50wt% of N-methylpyrrolidone and 50wt% of ethylene carbonate, and the components of the functional coating on the current collector provided with the functional coating include 50wt% of polyacrylic acid and 50wt% of conductive carbon black.
[0078] Example 3
[0079] This embodiment provides a silicon-based negative electrode and a preparation method thereof, wherein the silicon-based negative electrode comprises a current collector layer, a functionalized coating layer and a negative electrode active material layer stacked in sequence, the thickness of the functionalized coating layer is 2 μm, the thickness of the negative electrode active material layer is 60 μm, and the current collector is a copper foil;
[0080] The preparation method comprises:
[0081] (1) mixing the negative electrode active material, the first binder, the first conductive agent, the plasticizer and water to obtain a negative electrode active slurry having a solid content of 55% and a viscosity of 5500 cP;
[0082] (2) The negative electrode active slurry was coated on the current collector provided with the functionalized coating, dried, and hot rolled at 120°C at a rate of 6 m / min. The compacted density of the negative electrode sheet was 1.6 g / cm 3 , die cutting to obtain a silicon-based negative electrode;
[0083] The mass ratio of the negative electrode active material, the first binder, the first conductive agent and the plasticizer is 96:3:0.5:0.5, the negative electrode active material is 30wt% of silicon oxide and 70wt% of graphite, the first binder is 40wt% of polyacrylonitrile and 60wt% of styrene-butadiene rubber, the first conductive agent is 40wt% of conductive carbon black and 60wt% of carbon nanotubes, the plasticizer is 30wt% of ethylene glycol and 70wt% of ethylene carbonate, and the components of the functionalized coating on the current collector provided with the functionalized coating include 30wt% of polyacrylate and 70wt% of carbon nanotubes.
[0084] Example 4
[0085] This embodiment provides a silicon-based negative electrode and a preparation method thereof. The preparation method of this embodiment is the same as that of Example 1, except that the negative electrode active material in this embodiment is 15 wt % of silicon material and 85 wt % of graphite.
[0086] Example 5
[0087] This embodiment provides a silicon-based negative electrode and a preparation method thereof. The preparation method of this embodiment is the same as that of Example 1, except that the negative electrode active material in this embodiment is 20 wt % of silicon material and 80 wt % of graphite.
[0088] Embodiment 6-7
[0089] This embodiment provides a silicon-based negative electrode and a preparation method thereof. The preparation method of this embodiment is the same as that of Example 1, except that the hot rolling temperatures in this embodiment are 60° C. (Example 6) and 100° C. (Example 7).
[0090] Comparative Example 1
[0091] This comparative example provides a silicon-based negative electrode and a preparation method thereof. The preparation method of this comparative example is the same as that of Example 5, except that in step (2), the negative electrode active slurry is directly coated on the copper foil.
[0092] Comparative Example 2
[0093] This comparative example provides a silicon-based negative electrode and a preparation method thereof. The preparation method of this comparative example is the same as that of Example 5, except that no heating is performed during rolling in step (2).
[0094] Performance Test 1
[0095] The silicon-based negative electrodes obtained in Examples 1-7 and Comparative Examples 1-2 were subjected to a peeling force test. The test method was as follows: the electrode piece was cut into a strip with a length of 120 mm and a width of 25 mm using a flat cutter, and flatly attached to a steel plate with 3M double-sided adhesive tape. One end of the steel plate was fixed, and the other end was peeled off using a tensile tester to test the 180° peeling force. The results are shown in Figure 2. Figure 1 As shown in Table 1:
[0096] Table 1
[0097] project Peel force (N / m) Example 1 16.8 Example 2 14.0 Example 3 13.2 Example 4 14.8 Example 5 12.4 Example 6 15.6 Example 7 17.6 Comparative Example 1 6.4 Comparative Example 2 11.2
[0098] It can be seen from Table 1 that the peel strength of the silicon-based negative electrode obtained in the present application is between 1-20 N / m, and can preferably reach 10-20 N / m, which has good bonding performance.
[0099] Application Examples
[0100] The silicon-based negative electrodes obtained in Examples 1-7 and Comparative Examples 1-2 are assembled into a battery, comprising the following steps:
[0101] (1) mixing lithium nickel cobalt manganese oxide, PVDF, and conductive carbon black in a ratio of 95:3:2 in an N-methylpyrrolidone solvent to obtain a positive electrode active slurry, coating the mixture on a positive electrode current collector, and drying, rolling, and die-cutting the mixture to obtain a positive electrode sheet;
[0102] (2) Assembling the positive electrode plate and the silicon-based negative electrode, and obtaining a lithium battery after infiltration, formation, and capacity separation.
[0103] Performance Test 2
[0104] The lithium battery obtained in the application example was subjected to charge and discharge tests. The lithium-ion battery was charged to 4.3V at 0.33C, and then discharged to 2.75V at 0.33C to test the initial discharge specific capacity; the battery was then cycled under the conditions of a charge and discharge voltage of 2.75-4.3V and a charge and discharge current of 1C to test the discharge specific capacity, calculate the capacity retention rate, and test the DCR every 100 weeks.
[0105] The results are shown in Table 2:
[0106] Table 2
[0107]
[0108] As can be seen from Table 2, the lithium battery prepared using the silicon-based negative electrode of the present application has a high battery capacity, excellent capacity retention rate and cycle stability, a small increase in DCR during the cycle, and exhibits good kinetic characteristics, which can play an advantage in high-energy-density battery products.
[0109] Performance Test 3
[0110] The batteries prepared in Examples 1-7 and Comparative Examples 1-2 were disassembled to observe the negative electrode sheets. The disassembled negative electrode pictures of the batteries obtained from the silicon-based negative electrode of Example 5 are shown in FIG. Figure 2 As shown, the battery disassembly negative electrode obtained from the silicon-based negative electrode of Comparative Example 1 is shown in Figure 3 The results are shown in Table 3:
[0111] Table 3
[0112]
[0113]
[0114] It can be seen from Table 3 that the silicon-based negative electrode prepared in the present application has good adhesion, and the prepared negative electrode can be well used in batteries.
[0115] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0116] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a silicon-based negative electrode, characterized in that: The silicon-based negative electrode comprises a current collector, a functionalized coating and a negative electrode active material layer which are stacked in sequence; The preparation method comprises: compounding a negative electrode active material layer on a current collector provided with a functionalized coating by means of hot rolling.
2. The preparation method according to claim 1, characterized in that: The temperature of the hot roller pressing is 60-120°C, preferably 70-90°C; And / or, the speed of the hot rolling is less than 20 m / min; And / or, the pressure of the hot roller pressing is 1-10T; And / or, the compaction density of the hot roller is 1.3-1.65g / cm 3 .
3. The preparation method according to claim 1 or 2, characterized in that: The components of the negative electrode active material layer include a negative electrode active material, a first binder, a first conductive agent and a plasticizer; And / or, the components of the functionalized coating include a second conductive agent and a second binder.
4. The preparation method according to claim 3, characterized in that: The first conductive agent and the second conductive agent are each independently selected from any one or a combination of two or more of conductive carbon black, conductive carbon fiber, graphene, carbon nanotubes or Ketjen black, and preferably the first conductive agent and the second conductive agent contain the same component; And / or, the first binder and the second binder are each independently selected from any one or a combination of two or more of sodium carboxymethyl cellulose, polyacrylic acid, polyacrylate, polyacrylonitrile or styrene-butadiene rubber, and preferably the first binder and the second binder contain the same component; And / or, the negative electrode active material comprises graphite, or a combination of graphite and silicon material; And / or, the plasticizer is selected from any one or a combination of two or more of ethylene carbonate, N-methylpyrrolidone, ethylene glycol or isopropyl alcohol.
5. The preparation method according to any one of claims 3-4, characterized in that: The preparation method comprises: mixing a negative electrode active material, a first binder, a first conductive agent, a plasticizer and water to obtain a negative electrode active slurry, coating the negative electrode active slurry on a current collector provided with a functionalized coating, and then performing hot rolling.
6. The preparation method according to claim 5, characterized in that: The viscosity of the negative electrode active slurry is 2000-8000 cP; And / or, the solid content of the negative electrode active slurry is 25-55wt%; And / or, the coating surface density of the negative electrode active slurry is 50-200g / m 2 ; And / or, the mass ratio of the negative electrode active material, the first binder, the first conductive agent and the plasticizer is (90-99):(1-9):(0.5-5):(0.5-5), and the sum of the mass fractions of the components is 100wt%.
7. The preparation method according to any one of claims 4 to 6, characterized in that: Based on the total mass of the negative electrode active material being 100%, the content of the graphite is 50-100wt%, and the content of the silicon material is 0-50wt%.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The thickness of the functionalized coating is 0.5-2 μm; And / or, the thickness of the negative electrode active material layer is 50-150 μm; And / or, the current collector is selected from copper foil or aluminum foil.
9. The silicon-based negative electrode obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The peel strength of the silicon-based negative electrode is 1-20 N / m, preferably 10-20 N / m.
10. An electrochemical device, characterized in that: The electrochemical device comprises the silicon-based negative electrode according to claim 9.